Statistical Analysis of Cracks in The Internal Coating of the Pipe and Measurement Errors - Ibragimova, E.N. Ibragimova (Herald of Azerbaijan Engineering Academy, 2024)
Experiments and research shows that the presence of flaws, macro-micro cracks within the silicon coated pipes significantly reduces their operating period. The causes of these defects are associated with the lack of accuracy of the technological regime when applying to the internal surface of silicon coated pipes. The results of the CPC-based methods based on the proposed automated covering system and an advanced diagnostic device in previous studies were compared. The statistical errors of cracks have been identified. The article also shows the results of the study of the research, the percentage of the mikcocracks.